Visualizing social support in home pediatric palliative care using network maps. (March 2020) - Lindemann, Daniela; Borasio, Gian Domenico; Führer, Monika; Wasner, Maria
Background: Home care of children with life-limiting diseases is extremely challenging for parents/family caregivers and their social environment. In order to gain new insights into the perspective of family caregivers, we employed digital Network Maps for the first time in the field of pediatric palliative care. Aim: To examine whether the use of Network Maps helps to identify and visualize significant members of the social support system and the quality of the relationship, as well as the main areas of life that are experienced as being supportive by each individual. Design: The design was an integrated mixed methods study. Creation of Network Maps was assessed in conjunction with qualitative interviews. In addition, participants gave an oral feedback on the Network Maps themselves. Setting/participants: Parents of patients supported by a Specialized Home Pediatric Palliative Care team were eligible for inclusion. Forty-five parents were enrolled in the study. Results: All mothers and fathers were able to generate their individual Network Map without problems. The composition of the support systems differed greatly, even between members of the same family. Parents named on average 11 supporting actors, mainly family members and health care professionals. Some relationships were perceived as helpful and stressful at the same time. Conclusion: Network Maps appear to be an appropriate tool for the collection, reconstruction, and assessment of the current support situation of parents of dying children. Further studies should examine the usefulness of Network Maps for the understanding of the caregivers' support needs and for the development of psychosocial interventional strategies by pediatric palliative care teams.